Human talent management in companies - Herrera Granizo, Adriana Yamilet (2025)
This research was conducted at the Ecuadorian Ceramic Factory, located in the city of Riobamba, in the province of Chimborazo, Ecuador. Its purpose was to understand employee behavior in the performance of their duties. To this end, the importance of human capital in organizations was defined, and the various stages that must be carried out to ensure competent personnel are recruited prior to hiring were detailed. The objective is to obtain relevant information that contributes to achieving the organization's objectives. The goal is to contribute to maintaining optimal interpersonal relationships, allowing for the ongoing stability of the company and its employees. Consequently, it was necessary to examine various concepts, including the importance of human capital in organizations and human relations, referring to interpersonal interactions, classified as formal or informal, close or distant, emotional or non-emotional. In the corporate context, it is imperative to consider the existence of multiple types of relationships between individuals, such as individual interactions, interactions between owners, interactions between owners and employees, and interactions between employees and owners and customers. With these concerns in mind, a study was conducted to understand staff behavior in various contexts. The SWOT matrix, problem trees, and objective trees were used to establish a criterion that promotes harmony within the organization.